Nutrition and cognitive health: A life course approach - Puri, Seema; Shaheen, Majida; Grover, Bhanvi (Frontiers in Public Health, 2023)
Multiple factors affect cognitive health, such as age-related changes in the brain, injuries, mood disorders, substance abuse, and diseases. While some cannot be changed, evidence exists of many potentially possibly modifiable lifestyle factors: diet, physical activity, cognitive and social engagement, smoking and alcohol consumption which may stabilize or improve declining cognitive function. In nutrition, the focus has been mainly on its role in brain development in the early years. There is a strong emerging need to identify the role of diet and nutrition factors on age-related cognitive decline, which will open up the use of new approaches for prevention, treatment or management of age-related disorders and maintaining a good quality of life among older adults. While data on effect of high protein diets is not consistent, low-fat diets are protective against cognitive decline. Several micronutrients like B group vitamins and iron, as well as many polyphenols play a crucial role in cognitive health. Mediterranean, Nordic, DASH, and MIND diets are linked to a lower risk of cognitive decline and dementia. The relationship between the gut microbiome and brain function through the gut-brain axis has led to the emergence of data on the beneficial effects of dietary fibers and probiotics through the management of gut microbes. A “whole diet” approach as well as macro- and micro-nutrient intake levels that have protective effects against cardiovascular diseases are most likely to be effective against neurodegenerative disorders too. Young adulthood and middle age are crucial periods for determining cognitive health in old age. The importance of cardio metabolic risk factors such as obesity and hypertension, smoking and physical inactivity that develop in middle age suggest that preventive approaches are required for target populations in their 40s and 50s, much before they develop dementia. The commonality of dementia risk with cardiovascular and diabetes risk suggests that dementia could be added to present non-communicable disease management programs in primary healthcare and broader public health programs.